Safflower petal composition: impact of sowing time and plant density on proximate, antioxidants, and colorants - Cafaro, Valeria; Patanè, Cristina; Panebianco, Vivienne; Calcagno, Silvio; Caruso, Paolo; Testa, Giorgio (Frontiers in Plant Science, 2025)
IntroductionSafflower (Carthamus tinctorius L.) is a multipurpose plant that has recently attracted renewed interest as a natural source of antioxidant compounds and pigments from its petals, which can be used as alternatives to replace industrial compounds.MethodsIn a split-plot experimental design, the effects of three winter sowings (December, January, and February) and two plant densities (D1, 25 plants m−2; and D2, 50 plants m−2) on petal production and composition in nutrients and antioxidants, including colorants, were examined in safflower (cv. Catima) in a semi-arid Mediterranean environment. Petals were harvested twice: at the flowering of the main shoots (early harvest) and 1 week later, and at the flowering of the lateral shoots (late harvest).ResultsPetal production was reduced as sowing was shifted from December to February. The increase in plant density did not affect petals produced per plant but resulted in greater production per unit area. With sowing in January, crude protein was the highest (up to 17.2%), and oil content was the lowest (down to 3.72%). Total phenols significantly decreased (−6%) with the shift of sowing from December to February. Overall, they were accumulated to a greater extent at lower plant density (D1). Carthamidin (yellow pigment) was higher at the first harvest (up to 8.39%) and decreased thereafter, as carthamin (red pigment) was synthesized. Both pigments tended to decrease with the shift of sowing time and were lower in D1.DiscussionThe nutritional value was positively associated with the nutraceutical value. Greater contents in phenols, flavonoids, and carthamidin, with minor changes in the proximate composition of petals, can be achieved with sowings in late fall–early winter. Harvest at late flowering (~90% flowers open on lateral shoots) resulted in greater yields and carthamin content but lower petal quality, suggesting that the choice of the harvest time of petals strictly depends on the specific trait desired.